2020
DOI: 10.3390/su12041380
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Selection of the Machinery Park in Sustainable Agriculture

Abstract: A correct selection of the machinery park is vital for correct functioning of a farm. It is significant in sustainable farming where, except for economic factors, application of a suitable technique and technology in order to lead an effective production is crucial. The paper presents a method of designing a set of machines for a farm. The method was implemented in the computer application. A suitably selected, optimised machinery park enables a sustainable agricultural production and achievement of the desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Timely monitoring of agricultural production and accurate prediction of crop yield are crucial due to the severe economic and social consequences of food shortages [1,2]. Especially, agricultural products have to be increased by 70% by 2050, when the world population is expected to reach 9 billion people [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Timely monitoring of agricultural production and accurate prediction of crop yield are crucial due to the severe economic and social consequences of food shortages [1,2]. Especially, agricultural products have to be increased by 70% by 2050, when the world population is expected to reach 9 billion people [3].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the spectral features at the flowering stage has not been considered in rice yield estimation, although some researchers have observed that the presence of flowers can cause canopy spectral changes in certain bands [29,30]. At present, research on remote sensing monitoring of flowering can be categorized into three types: (1) the extraction of floret amount information (flower coverage ratio and flower number) basing on remote sensing data. Thorpa et al [31] estimated the floret number of leskelaole rape by flower coverage proportion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly proposed approach to the design of the machine-tractor fleet is based on heuristic methods and is very laborious [4]. In some Eastern European countries, it is proposed to determine the necessary equipment on the basis of the so-called reference tractor or using specific software [5][6][7]. Unfortunately, these methods are not suitable for small farms due to the high inaccuracy of input information, the use of aggregated economic indicators or the unavailability of relevant application programs.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of machinery and operator costs could be estimated for each field, or subsection, instead of using some type of aggregated average. Applying conventional machinery management models with DGPS data for round baling operations provides the basis for analysis and simulation of the harvest of high-yielding bioenergy crops [10][11][12].…”
Section: Introductionmentioning
confidence: 99%